STATE OF NITRIC OXIDE SYSTEM IN PATIENTS WITH PEPTIC ULCERS IN COMBINATION WITH HYPERTENSIVE ILLNESS - Zheleznyakova, N. M.; Pasieshvili, L. M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The article is devoted to the study performance of NO in patients with duodenal ulcer associated with H. pylori, in combination with hypertension. A thorough analysis of these indices in the combined and isolated course of peptic duodenal ulcer and hypertension. Revealed correlations between the levels of NO metabolites and severity of morphological changes in the mucosa of the stomach and duodenum, the degree of contamination of H.pylori, the presence of gastroesophageal and / or duodenogastric reflux and stage of hypertension in these patients.